Applying the theory of constraints to the logistics service of medical records of a hospital - Víctor G. Aguilar-Escobar; Pedro Garrido-Vega; María-del-Mar González-Zamora (European Research on Management and Business Economics (ERMBE), 2016)
Management of patient records in a hospital is of major importance, for its impact both on the quality of care and on the associated costs. Since this process is circular, the prevention of the building up of bottlenecks is especially important. Thus, the objective of this paper was to analyze whether the Theory of Constraints (TOC) can be useful to the logistics of medical records in hospitals. The paper is based on a case study conducted aboutthe 2007-2011 period in the Medical Records Logistics Service atthe Hospital Universitario Virgen Macarena in Seville (Spain). From April 2008, a set of actions in the clinical record logistics system were implemented based on the application of TOC principles. The results obtained show a significant increase in the level of service and employee productivity, as well as a reduction of cost and the number of patients complaints. – – La gestión del archivo de historias clínicas en un hospital tiene trascendencia por su incidencia en la calidad asistencial y en los costes. Este es un proceso circular, por lo que prevenir la aparición de cuellos de botella es especialmente importante. De esta forma, el objetivo de este trabajo es analizar si la Teoría de las Limitaciones (TOC) puede ser útil para la logística de historias clínicas. El trabajo se centra en un estudio de caso sobre el Servicio de Logística de Documentación Clínica del Hospital Universitario Virgen Macarena de Sevilla en el periodo 2007-2011. Desde 2008 se desarrolló un conjunto de actuaciones en dicho servicio basado en la aplicación de principios TOC. Los resultados obtenidos muestran un aumento significativo del nivel de servicio y de la productividad de los empleados, así como una reducción del coste y del número de reclamaciones de los pacientes.
Keywords: I1; M11; 650; Health; Production Management; Theory of Constraints; Medical Records; Salud; Gestión de la Producción; Teoría de las limitaciones; Historias clínicas